2023
DOI: 10.3389/fendo.2023.1232143
|View full text |Cite
|
Sign up to set email alerts
|

Metformin targets intestinal immune system signaling pathways in a high-fat diet-induced mouse model of obesity and insulin resistance

Monta Brīvība,
Laila Silamiķele,
Ineta Kalniņa
et al.

Abstract: IntroductionResearch findings of the past decade have highlighted the gut as the main site of action of the oral antihyperglycemic agent metformin despite its pharmacological role in the liver. Extensive evidence supports metformin’s modulatory effect on the composition and function of gut microbiota, nevertheless, the underlying mechanisms of the host responses remain elusive. Our study aimed to evaluate metformin-induced alterations in the intestinal transcriptome profiles at different metabolic states. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Similarly, the mechanism of insulin resistance stems from the interaction between gut microbiota and host genes. Previous studies reported that the lipid diet-induced gut microbiota, including Parabacteroides distasonis , Bacteroides spp., and Lactobacillus spp., could reduce the NF-κB gene expression level as well as the levels of pro-inflammatory Th17 cells in the gut tissues ( Ang et al., 2020 ; Brīvība et al., 2023 ). The current study found that the cecal host genes involved in the calcium signaling pathway and PI3K-Akt signaling pathway were upregulated, while those involved in the NF-κB signaling pathway and T cell receptor signaling pathway were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the mechanism of insulin resistance stems from the interaction between gut microbiota and host genes. Previous studies reported that the lipid diet-induced gut microbiota, including Parabacteroides distasonis , Bacteroides spp., and Lactobacillus spp., could reduce the NF-κB gene expression level as well as the levels of pro-inflammatory Th17 cells in the gut tissues ( Ang et al., 2020 ; Brīvība et al., 2023 ). The current study found that the cecal host genes involved in the calcium signaling pathway and PI3K-Akt signaling pathway were upregulated, while those involved in the NF-κB signaling pathway and T cell receptor signaling pathway were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, metformin has demonstrated anti-inflammatory effects through the inhibition of IL-18 expression, which is linked to alterations in the intestinal microbiome (Lee et al, 2019). Another study found that treatment with metformin can regulate the immune response in the intestines of mice by altering the composition of the gut microbiome, particularly through the downregulation of the NF-κB signaling pathway (Brīvība et al, 2023). Therefore, metformin potentially enhances immune responses by modulating the gut microbiota.…”
Section: Modulation Of Immune Responsementioning
confidence: 99%